Nivel de Captación y Retención de Clientes de la Cooperativa de Ahorro y Crédito San José del Cantón Montalvo - Elaje Miranda, Katty Patricia (2017)
Currently, Ecuador is the second country in Latin America to have more credit and savings cooperatives, with a total of 887 entities behind Brazil, where there are 1332 financial institutions. Cooperativism arises at the beginning of the twentieth century and from there faced major obstacles but that has not prevented the sector to flourish and which is now considered as a valid tool for social development